Basic poly(propylene glycols) as reference compounds for internal mass calibration in positive-ion matrix-assisted laser desorption/ionization mass spectrometry - Gross, Jürgen H. (European journal of mass spectrometry, 2017)
Basic poly(propylene glycols), commercially available under the trade name Jeffamine, are evaluated for their potential use as internal mass calibrants in matrix-assisted laser desorption/ionization-time-of-flight-mass spectrometry. Due to their basic amino endgroups Jeffamines are expected to deliver [M+H]+ ions in higher yields than neutral poly(propylene glycols) or poly(ethylene glycols). Aiming at accurate mass measurements and molecular formula determinations by matrix-assisted laser desorption/ionization-time-of-flight-mass spectrometry, four Jeffamines (M-600, M-2005, D-400, D-230) were thus compared. As a result, Jeffamine M-2005 is introduced as a new mass calibrant for positive-ion matrix-assisted laser desorption/ionization-time-of-flight-mass spectrometry in the range of m/z 200-1200 and the reference mass list is provided. While Jeffamine M-2005 is compatible with α-cyano-4-hydroxycinnamic acid, 2,5-dihydroxybenzoic acid, and 2-[(2E)-3-(4-tert-butylphenyl)-2-methylprop-2-enylidene]malonitrile matrix, its use in combination with 2-[(2E)-3-(4-tert-butylphenyl)-2-methylprop-2-enylidene]malonitrile provides best results due to low laser fluence requirements. Applications to PEG 300, PEG 600, the ionic liquid trihexyl(tetradecyl)-phosphonium tris(pentafluoroethyl)-trifluorophosphate, and [60]fullerene demonstrate mass accuracies of 2-5 ppm.